ProLife answers to proChoice arguments - Alcorn, Randy C. (Sisters, Or. : Multnomah Publishers, 2000)
Presents opposing views or "answers" to many arguments used by the Pro-Choice movement as to why abortion should be legal in the United States.
Part 1. Arguments concerning life, humanity, and personhood -- Part 2. Arguments concerning rights and fairness -- Part 3. Arguments concerning social issues -- Part 4. Arguments concerning health and safety -- Part 5. Arguments concerning the hard cases -- Part 6. Arguments against the character of prolifers -- Summary argument -- Final appeals.
Keywords: Pro-life movement -- United States -- Handbooks, manuals, etc; Abortion -- United States -- Handbooks, manuals, etc; Abortion; Pro-life movement; United States; Handbooks, manuals, etc